n Afrikanerperspektief op die Groot Trek : simbool en ritueel (Historia, 2021)
An Afrikaner perspective on the Great Trek: Symbol and Ritual. This deals with Great Trek historiography from the Afrikaner point of view. It is a critical analysis of the changing perceptions of this ""central"" event in the historical consciousness of the Afrikaner people which reminds of Tacitus' dictum, ""Maior est longinquo revenrentia"". It became a symbol and through the ""Day of the Vow"" a yearly ritual. In the Trek the nationalistic-minded Afrikaners found their self-image and mythology. The relationship between historical and national consciousness is demonstrated. Their historical consciousness reflects a time-structure of future expectation which determined the interpretation of the past and understanding of the present. Its functions were the legitimising of Afrikaner existence, culture and policy, orientation in South Africa and the world, and supporting of their identity as a people. The pre-scientific phase is divided into three periods: short term perspectives (contemporary self-understanding), medium term perspectives conceived from the late 19th century ""racial"" conflict between Boer and Briton, and long term perspectives of the 20th century (nationalistic and political weaponry, parochialism, and narcissism!. Then follows the scientific phase: An analysis of the historical consciousness which was determined by nationalistic and party interests, nostalgia and empathy with Afrikaner ideals and currently a more realistic and demythologising attitude amongst some prominent historians.
Keywords: Day of the Covenant; Great Trek; Historiography; History; Afrikaners; Symbolism